Catalytic olefin polymerization proceedings of the International Symposium on Recent Developments in Olefin Polymerization Catalysts, Tokyo, October 23-25, 1989 (Studies in surface science and catalysis, 1990)
Recent development of a new generation of Ziegler-Natta Catalysts using either magnesium dichloride as carrier or methylaluminoxane as cocatalyst has markedly stimulated the research activity in the field of olefin polymerization. These discoveries have not only yielded economical processes for polyolefin production but also opened the way to a new generation of novel polymers. Moreover, the nature of active species is being clarified well by the effort to simplify catalyst systems. The present volume includes 38 papers from the 31 lectures and 18 posters presented at the symposium on 'Recent Developments in Olefin Polymerization Catalysts', which covered the following topics: Overview of super-active homogeneous and heterogeneous catalysts, kinetic profile of olefin polymerization including copolymerization, characterization of catalysts and polymers, methods for the determination of active center concentration, role of Lewis bases on the catalysts isospecificity, polymerization mechanisms, and synthetic pathways for functionalized polyolefins. The contents are well balanced between fundamental research and application as well as between homogeneous and heterogeneous catalyst systems